For #2:
<span> 3x^2 + 4 – 2x^2 + 6</span>
<span><span>You need to combine your like terms:
</span>
3x^2 – 2x^2= x^2</span>
4 + 6 = 10
This will now give you:
<span>X^2 +10</span>
Answer:
y=(y\x - 10j\x) x+j•10
Step-by-step explanation:
its up there
Answer:
1 unit to the right
Step-by-step explanation:
The y-axis is the vertical line and the point (1,-3) is one unit to the right of the vertical line
Ship fast equation for n packages:
2n+(1)x
where x the weight of the packages
Speedy delivery equation for the number of packages:
3n+(0.50)x
The same price happened when:
2n+(1)x = 3n+(0.50)x
x - 0.5x=3n - 2n
x = n/0.5
x = 2n
when the package weight is 2 pounds
The answer is [($109.90-$98.91)/$109.90]X100%